Local Structure and Proton Transport in HT-PEFCs Measured with Neutron Scattering. (14th September 2015) - Holderer, Olaf; Ivanova, Oxana; Khaneft, Marina; Hopfenmüller, Bernhard; Lüke, Wiebke; Majerus, Anne; Appavou, Marie-Sousai; Szekely, Noemi; Krutyeva, Margarita; Kentzinger, Emmanuel; Zorn, Reiner; Lehnert, Werner
Abstract : The structural properties and proton transport processes of High Temperature Polymer Electrolyte Fuel Cells (HT-PEFCs) are studied on a broad range of length- and timescales with different neutron scattering techniques. We show structural properties of the proton conducting membrane and of the catalyst layer. Proton transport is measured with quasielastic neutron scattering techniques. The sensitivity of neutrons to individual isotopes, especially in the case of hydrogen and deuterium, makes neutron scattering a perfect tool for such studies. Complementary techniques such as transmission electron microscopy, PFG-NMR and X-ray scattering round up the picture of the different fuel cell components.